Suitability of Electrical Resistivity Survey for Selecting Anicut Site in order to Augment Ground Water-A Case Study - Shukla, J P; Pandey, S M (Annals of Arid Zone, 2016)
Vertical Electrical Soundings (VES) using schlumberger configuration were conducted at three anicut sites at villages Binjwaria, Rampura and Manaklao, on Rampura rivulet, originating from Binjwaria of district Jodhpur. A total of 162 VES data were obtained along and across the main stream. A close distribution of observation has enabled mapping of sub surface topography. In order to augument the ground water of Ihe area, three anicuts on this rivulet are proposed. Resistivity parameters reveal that sandstone is likely to encounter shallow depth at Binjwaria and therefore it is the best suitable site for anicut. Gradually depth to sandstone increases towards Manaklao as evident by the fence diagram. Hence suitability of constructing anicut in this direction is less.